Analysis of the Effect of Blended Learning Model on Employee Class Students Learning Motivation - Kifta, Decky Antony; Riyanda, Afif Rahman; Simatupang, Wakhinuddin; Muskhir, Mukhlidi; Irfan, Dedy (FKIP Universitas Lampung, 2021)
Blended learning is a learning approach that combines online educational materials with traditional classroom-based methods. The traditional learning model requires the physical presence of lecturers and students, especially those trying to take further education with the employee class program, because they have to manage their time between study, work and even family. This study evaluates how the effect of using the blended learning model on the student's motivation to learn in the employee class. The study uses quantitative method with quasi experimental design. The design which utilizes one-group pretest-posttest with control group design, namely a research design that contains a pretest, before blended learning is carried out, and posttest after blended learning is carried out. The results of the study show that there is significant effectiveness of using the blended learning model compared to traditional towards the motivation of the employee class students.Keywords: blended learning, learning motivation, employee class students. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp226-234